1998
DOI: 10.1007/s000000050102
|View full text |Cite
|
Sign up to set email alerts
|

Entropy solutions for weakly coupled hyperbolic systems in several space dimensions

Abstract: Systems of nonlinear hyperbolic conservation laws in several space dimensions are considered which are characterized by the fact that the coupling of the equations is only due to source terms. These weakly coupled systems arise in a variety of applications like hydrological problems, the theory of reactive flows, relaxation schemes, or mathematical biology. We present an existence and uniqueness theorem for certain entropy solutions of a general class of weakly coupled hyperbolic initial value problems. The ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…It was shown in Reference [25] that under the above assumptions a unique entropy solution u of (26) and (27) exists. Now let us describe the numerical scheme for which we will show an a posteriori result.…”
Section: Deÿnition 2 (Entropy Solution)mentioning
confidence: 96%
See 1 more Smart Citation
“…It was shown in Reference [25] that under the above assumptions a unique entropy solution u of (26) and (27) exists. Now let us describe the numerical scheme for which we will show an a posteriori result.…”
Section: Deÿnition 2 (Entropy Solution)mentioning
confidence: 96%
“…In a forthcoming paper [26] this result will be generalized to weakly coupled systems as in Reference [27]. Then the mathematical model for the biodegradation (1), (2) and (3) will be covered by this generalization.…”
Section: Remarkmentioning
confidence: 99%
“…2 Remark 3.11. In [14], it was proven that entropy solutions of weakly coupled systems like (2.8) are unique if they exist. Thus, the last proof shows the convergence of the difference scheme (3.2) to the unique entropy solution of the Cauchy problem (2.8).…”
Section: Existence Of Entropy Solutionsmentioning
confidence: 99%
“…In the following we present a summary of the existing work done in this field to the best of our knowledge. First, there is the Euclidean case where the weakly coupled systems are considered as Cauchy problems on R 2 in Levy [25] and Rohde [38] or later in several space dimensions in Rohde [39]. Here the authors looked at the model introduced by Majda, that can be found in [29].…”
Section: Introductionmentioning
confidence: 99%